Tetrabromobisphenol A - Toxicity, environmental and occupational exposures - Monika Jarosiewicz; Bożena Bukowska (Nofer Institute of Occupational Medicine, 2017)
Brominated flame retardants (BFR), including tetrabromobisphenol A (TBBPA) represents 25% of the global market of flame retardants. Among them, TBBPA is used on the largest scale (approx. 60%) because of its firebreak properties and widespread occurrence in every day products such as furniture, upholstery, adhesives and electronic equipment. A broad application of TBBPA can contribute to environmental pollution. Tetrabromobisphenol A has been determined in soil, water, river sediments and the atmosphere. Tetrabromobisphenol A is characterized by a high value of coefficient n-octanol/water (log P = 4.5), low acidity, and it may exist in undissociated or dissociated form. Due to the high hydrophobicity, TBBPA may accumulate in living organisms, including humans at different food chain levels. The occurrence of TBBPA in humans, e.g., in blood, fat tissue and mother milk, has been reported. Tetrabromobisphenol A is classified as hazard statements (H) H400/H410, which means that it is toxic to aquatic biota, causing long-term changes in these organisms. Up to now, only a few studies have been conducted to assess potential toxicity of high doses of TBBPA to mammals. Although many people are occupationally exposed to TBBPA during production or processing of this substance in their workplaces, there are only a few studies that have assessed the real hazard associated with TBPPA exposure. The aim of the study was to discuss the latest literature (mainly from the years 2010-2016) referring to the presence of TBBPA in the environment and its effects to living organisms. Data concerning occupational exposure to TBBPA were also presented. Med Pr 2017;68(1):121-134